Abdominal obesity and structure and function of the heart in healthy male Koreans: The ARIRANG study. Issue 39 (September 2016) - Son, Jung-Woo; Sung, Joong Kyung; Lee, Jun-Won; Youn, Young Jin; Ahn, Min-Soo; Ahn, Sung Gyun; Yoo, Byung-Su; Lee, Seung-Hwan; Yoon, Junghan; Koh, Sang Baek; Kim, Jang-Young
Abstract : Abstract: Although central obesity is a more powerful predictor of cardiovascular disease (CVD) than general obesity, there is limited information on structural and functional changes of the heart in central obesity. Therefore, we evaluated the association between abdominal obesity and geometric and functional changes of the heart in healthy males. A total of 1460 healthy males aged 40 to 70 years without known CVD from the Korean Genome and Epidemiology Study on Atherosclerosis Risk of Rural Areas in the Korean General Population were included. All individuals underwent conventional 2-dimensional echocardiography and tissue Doppler imaging to measure left atrial (LA) and left ventricle (LV) geometry and function. Increasing tertiles of waist circumference (WC) were associated with stepwise increases in LA volume, LV end-diastolic dimension, LV mass to height 2, deceleration time of E wave, and lower E/A ratio (all P trends <0.001). In multivariable logistic regression models, the odds ratios for LA enlargement, LV hypertrophy, LV enlargement, and diastolic dysfunction comparing the upper tertile of WC (>89 cm) to the lowest tertile (<82 cm) were 2.81 (95% confidence interval [CI] 2.24–3.54), 3.65 (95% CI 2.54–5.26), 4.23 (95% CI 2.61–6.87), and 1.75 (95% CI 1.37–2.22), respectively. LV ejection fraction and relative wall thickness were not increased with increasing WC. The association between WC and LA enlargement, LV enlargement, and diastolic dysfunction persisted after stratification by body mass index tertiles. Central obesity may be a stronger predictor than general obesity of geometric and functional changes in the LV and LA.